Model Perancangan Sistem Informasi Akuntansi Laporan Keuangan Pondok Pesantren Berbasis SAK ETAP - S Supriyati; Ramadhan Syaeful Bahri (Labkat Press KA FTIK UNIKOM, 2019)
The research objective is to make a Model of Accounting Information System Design for Financial Statements of SAK ETAP-based Islamic Boarding Schools to facilitate Islamic Boarding Schools in processing finance quickly and accurately and based on SAK ETAP so that Financial Statements and Financial Records are carried out in accordance with the references issued by IAI in the Accounting Guidebook Boarding school. This is important because the purpose of making the pesantren accounting handbook is part of efforts to empower the pesantren's economy so that the boarding school is able to prepare financial reports based on generally accepted financial accounting standards in Indonesia and is supported by an information system so that financial records can be carried out easily. The unit of analysis examined in this study were 3 Islamic Boarding Schools in Bandung, namely Nurul Amanah Islamic Boarding School Cisaranten Kulon, Al Falah Dago Islamic Boarding School, and Al Burhan Islamic Boarding School Cigadung. The research method used by researchers is descriptive, explorative, and survey research methods. The population studied in this study were the financial books and records of the Nurul Amanah Islamic Boarding School transactions from 2009 to 2018, the financial books of the Al Falah Islamic Boarding School in 1950 to 2018, the financial books of the Al Burhan Islamic Boarding School in 1950 to 2018. The sample used was financial records and transaction records of Nurul Amanah Islamic Boarding School from 2017 to 2018, financial accounting of Al Falah Islamic Boarding School and Al Burhan Islamic Boarding School from 2017 to 2018. The results of this study are the design of Accounting Information System Information for Financial Statements with Model Use Case Diagram, Activity Diagram, ERD.